ARE RURAL HOUSEHOLDS WILLING TO PAY FOR CLEAN ENERGY? EVIDENCE FROM SOUTH WEST NIGERIA (2017)
Modern energy services such as electricity offer social, economic and health benefits, particularly for rural households that depend wholly and solely on traditional fuels. Insight into rural household preferences and willingness to pay for clean energy is a key variable for suppliers to become more competitive in the retail market and for government to design energy policies. Therefore, this study was carried out to assess consumers’ willingness to pay for renewable energy source(s) in Kajola Local Government Area of Oyo State. A multistage sampling procedure was employed to sample 200 household in the study area. Data was analysed using descriptive statistics, Likert scale and the logit model. Results showed that a majority of the respondents were willing to pay for improved hydro-electricity (71%) and solar lamps (58.5%) while about 13% and 27.5% of them were willing to pay for solar PV and biomass respectively. Further, the logit models revealed that bid, age, sex, marital status, household size, per capital expenditure and year of education were the prime drivers of respondents’ willingness to pay for clean energy. The respondents were willing to pay for clean energy source given that the prices were not too high.